CONTRIBUTIONS TO THE KNOWLEDGE OF CAMBODIAN CYPERACEAE - Tremetsberger, K.; Hameister, S.; Simpson, D. A.; Bernhardt, K.-G. (Edinburgh Journal of Botany, 2019)
To date, there are very few sequence data for Cyperaceae from mainland Southeast Asia. The aim of the present study was to contribute nuclear ribosomal internal transcribed spacer (ITS) sequences of selected species of Cambodian Cyperaceae to the overall phylogeny of the family. We generated ITS sequences of 38 accessions representing 26 species from Cambodia and used these sequences for phylogenetic analysis together with similar sequences from the National Center for Biotechnology Information GenBank. Our results corroborate recent phylogenetic work in the family and largely confirm established tribal relationships. The backbone of the phylogenetic tree of species-rich genera that have undergone rapid radiations is often weakly resolved (e.g. in Fimbristylis and in the C4 clade of Cyperus). Cryptic variation was revealed in the taxonomically difficult group of Fimbristylis dichotoma, with samples of this taxon appearing in two distinct clades within Fimbristylis. Further addition of geographically spread accessions of taxa will improve our understanding of the complex biogeographical history of the genera in the family. Eleocharis koyamae Tremetsb. & D.A.Simpson is proposed as a new name for E. macrorrhiza T. Koyama.